Association of Sicca Syndrome with Proviral Load and Proinflammatory Cytokines in HTLV-1 Infection - Clara Mônica Lima; Silvane Santos; Adriana Dourado; Natália B. Carvalho; Valéria Bittencourt; Marcus Miranda Lessa; Isadora Siqueira; Edgar M. Carvalho (Journal of Immunology Research)
The Sjögren syndrome has been diagnosed in patients with HTLV-1 associated myelopathy and dry mouth and dry eyes are documented in HTLV-1 carriers. However the diagnosis of Sjögren syndrome in these subjects has been contested. In this cross-sectional study, we evaluated the role of immunological factors and proviral load, in sicca syndrome associated with HTLV-1 in patients without myelopathy. Subjects were recruited in the HTLV-1 Clinic, from 2009 to 2011. The proviral load and cytokine levels (IFN-γ, TNF-α, IL-5, and IL-10) were obtained from a database containing the values presented by the subjects at admission in the clinic. Of the 272 participants, 59 (21.7%) had sicca syndrome and in all of them anti-Sjögren syndrome related antigen A (SSA) and antigen B (SSB) were negatives. The production of TNF-α and IFN-γ was higher in the group with sicca syndrome (P<0.05) than in HTLV-1 infected subjects without sicca syndrome. Our data indicates that patients with sicca syndrome associated with HTLV-1 do not have Sjögren syndrome. However the increased production of TNF-α and IFN-γ in this group of patients may contribute to the pathogenesis of sicca syndrome associated with HTLV-1.